Iodine‐Mediated Nucleophilic Direct Oxidative α‐Acetoxylation and α‐Alkoxylation of Ketones. Issue 42 (13th November 2019) - Pogaku, Naresh; Krishna, Palakodety Radha; Prapurna, Y. Lakshmi
Abstract: A general and facile approach for the direct α‐functionalization of ketones mediated by iodine is developed. The operational simplicity, easily available starting materials, mild reaction conditions and tolerance of wide range of functional groups are the major benefits of the reaction. Abstract : An iodine‐mediated simple method for the α‐acetoxylation and α‐alkoxylation of Ketones has been developed. The practicability of this method is highlighted by easily accessible reagents, broad substrate scope and shorter reaction times. The reaction proceeds under mild reaction conditions and provides an alternative strategy for the oxidative α‐functionalization of ketones.